Gene expression patterns of helicoverpa armigera gut proteases - Chougule, Nanasaheb P.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Insect Biochemistry and Molecular Biology, 2005)
Relative quantification of reported gut proteinase cDNAs from Helicoverpa armigera larvae fed on various host plants (cotton, chickpea, pigeonpea, tomato and okra), non-host plant Pis (winged bean, bitter gourd, ground nut, and capsicum) and during larval development has been carried out using semi-quantitative RT-PCR. Five trypsin-like and three chymotrypsin-like proteinases were categorized as insensitive or sensitive to most of the proteinase inhibitors (Pis) and insensitive/sensitive to specific Pis based on their expression analysis. These results were supported by amino acid sequence analysis, where diverged amino acids were observed in the regions, which are reported to be involved in typical trypsin trypsin inhibitor interactions and critical for proteinase inhibitor resistance. Among exopeptidases (five aminopeptidase and three carboxypeptidase), HaAmi4 and HaAmi5 of aminopeptidase and HaCar1 of carboxypeptidase exhibited considerable differential expression. Elastase and cathepsin B-like proteinases were expressed at negligible levels. The proteases identified in the study would be ideal candidates for further interactions studies with protease inhibitors to understand the structural reasons of protease inhibitor insensitivity (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: expression; gut proteinases; Helicoverpa armigera; Proteinase inhibitors; RT-PCR

Higher accumulation of proteinase inhibitors in flowers than leaves and fruits as a possible basis for differential feeding preference of Helicoverpa armigera on tomato (Lycopersicon esculentum Mill, Cv. Dhanashree) - Damle, M. S.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Phytochemistry, 2005)
Tomato (Lycopersicon esculentum, Mill; cultivar- Dhanashree) proteinase inhibitors (Pis) were tested for their trypsin inhibitory (TT) and Helicoverpa armigera gut proteinases inhibitory (HGPI) activity in different organs of the tomato plants. Analysis of TI and HGPI distribution in various parts of the plant showed that flowers accumulated about 300 and 1000 times higher levels of TI while 700 and 400 times higher levels of HGPI as compared to those in leaves and fruits, respectively. Field observation that H. armigera larvae infest leaves and fruits but not the flowers could be at least partially attributed to the protective role-played by the higher levels of Pis in the flower tissue. Tomato Pis inhibited about 50-80% HGP activity of H. armigera larvae feeding on various host plants including tomato, of larvae exposed to non-host plant Pis and of various larval instars. Tomato Pis were found to be highly stable to insect proteinases wherein incubation of inhibitor with HGP even for 3 h at optimum conditions did not affect inhibitory activity. Bioassay using H. armigera larvae fed on artificial diet containing tomato PIs revealed adverse effect on larval growth, pupae development, adult formation and fecundity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: accumulation of PI; Helicoverpa armigera; Lycopersicon esculentum; Midgut proteinases; Plant defense; Proteinase inhibitors

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors